Analisis Sosial Ekonomi Terhadap Pasar Tenaga Kerja Wanita Yang Bekerja Di Sumatera Barat - Marwah Uswah Rotania Irfan; Yeniwati (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research uses secondary data sourced from the SAKERNAS National Labor Force Survey, (2022) from the Indonesian Central Statistics Agency. This research aims to determine the influence of education, marital status, age, and regional on female workers working in West Sumatra. This type of research is quantitative research. This research uses the Logistic Regression analysis method. Based on the results of the analysis and hypothesis testing, it was found that the Education and Region variables had a positive and significant influence on the female workforce working in West Sumatra. Meanwhile, the age variable had a negative and significant influence on the female workforce working in West Sumatra, then the Marital Status variable was not significant on the workforce. Women working in West Sumatra.